EXPLORING THE CORRELATION BETWEEN CULTURAL INTELLIGENCE AND WRITING PERFORMANCE AMONG EFL LEARNERS - Mega Aulia Ardhi; Desi Surlitasari Dewi; Adam (Universitas Islam Ogan Komering Ilir Kayuagung, 2025)
This study explores the relationship between Cultural Intelligence (CQ) and writing performance among EFL learners, motivated by the rising importance of intercultural competence in English education. Using a quantitative correlational design, data were collected from 26 first-semester students through the Cultural Intelligence Scale (CQS) and a writing performance test requiring an opinion paragraph. After confirming data normality, hypothesis testing with the Pearson Product-Moment correlation revealed a significance value of 0.830 (p > 0.05), indicating no significant correlation between CQ and writing performance. The findings suggest that writing proficiency is more strongly influenced by technical factors such as grammatical accuracy, vocabulary range, coherence, organization, and writing experience, rather than by cultural intelligence alone. These results challenge assumptions about the universal impact of CQ on language skills and highlight the necessity of targeted interventions focused on enhancing core writing competencies. Future studies are encouraged to examine moderating variables such as learner motivation, cultural exposure, and instructional methods to better understand the nuanced relationship between cultural intelligence and writing performance in EFL contexts